Urban Residential Demand for Water in Subang Jaya, Selangor: A Cross-Sectional Analysis - Annaniah, Remee Dass (1999)
Water resource management and development has become a much discussed topic in the last three decades, engaging the attention of not only engineers, planners and decision makers, but also the general public. Malaysia's water resources are under great strain as a result of rapid population growth, agricultural, industrial and commercial development and reduced rainfall in some areas. It is expected that water consumption will increase at least three fold by the year 2000. Considerable evidence shows that water conservation as an alternative is often a more cost effective than investment in additional capacity. Water resource economists, in particular, have become interested in understanding the empirical nature of water demand for forecasting of water demand, pricing and in improving water resources planning and management. Recent controversies have been on the appropriate price specification and the estimation of elasticities under block rate pricing. Many economists have come forward with many challenging models and have justified their choice with empirical evidence. In this study, price elasticity of demand for residential water is estimated for consumers in Subang Jaya, Selangor. The AP and FIP specification regression models using both linear and semilog functional forms are run for a cross-sectional sample of 173 households. The results showed that the price, income and household size elasticities are in the range of -0.56 to -0.97, 0.12 to 0.29 and 0.37 to 0.99 respectively. Compared to AP, the FIP specification which incorporates MP and D, was found to be a better choice for the price variable in the residential water demand models. In all cases except price, the AP model overestimated the change in consumption of water when there is a change in one of the explanatory variables (income, household size). Social, cultural and religious practices were not found to affect the consumption patterns of three different ethnic groups in Subang Jaya. This only shows that many city dwellers have adopted life style common for all ethnic groups living in Malaysia. Price, income and household size elasticities estimated for 5 different income groups using PIP specification were in the range of -1.18 to 1.98, negligible, and 0.48 to 1.11 respectively. The price elasticities obtained for some of the income groups however were inconsistent and had positive signs. Results of Shin's Price Perception Model showed that consumers were not responsive to either average price or marginal price in all cases except the very high income group responsiveness declines with increases in the income level of households. Results of this study showed that elasticities of explanatory variables can be used as an effective policy instrument by water utilities in the planning and allocation of water supplies. Water conserved through pricing and management policies would be more cost effective than financing storage capacity expansion. Future research work should look at the exact relationship between price change and storage capacity reduction. In particular, the price elasticity estimates and supply management by using appropriate pricing policy for urban consumers, would help policymakers to manage water resource efficiently.